1998
DOI: 10.1287/mnsc.44.7.896
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Channels: An Extension of Exclusive Retailership

Abstract: The underlying channel structure in most studies to date has consisted either of exclusive dealers that sell only one manufacturer's brand or of a single retailer selling multiple brands. Little attention has been given to the larger segment of most consumer goods markets in which retailers compete to sell multiple brands at the same location. This research seeks to add to the growing literature of channel competition by analyzing three channel structures, the least constrained of which deals with two competin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(105 citation statements)
references
References 16 publications
1
101
3
Order By: Relevance
“…(Jeuland and Shugan, 1983). VI can lower retail prices for other channel structures as well -upstream monopolists selling through multiple downstream monopolists (Romano, 1987), a duopoly channel structure with exclusive dealers (McGuire and Staelin, 1983;Coughlan, 1985), and a "Full Channel" structure with two competing manufacturers both selling through both competing retailers (Trivedi, 1998) 10 .…”
Section: Vertical Integration and Decentralizationmentioning
confidence: 99%
See 2 more Smart Citations
“…(Jeuland and Shugan, 1983). VI can lower retail prices for other channel structures as well -upstream monopolists selling through multiple downstream monopolists (Romano, 1987), a duopoly channel structure with exclusive dealers (McGuire and Staelin, 1983;Coughlan, 1985), and a "Full Channel" structure with two competing manufacturers both selling through both competing retailers (Trivedi, 1998) 10 .…”
Section: Vertical Integration and Decentralizationmentioning
confidence: 99%
“…This is because marketing middlemen soften manufacturer competition as the effect of a price change by a manufacturer on final retail demand is weakened by the intermediary. Other channel restraints such as exclusive dealing (Trivedi, 1998) and exclusive territories (Rey and Stiglitz, 1995) can also reduce manufacturer competition. Moorthy (1988) showed that retail competition is not necessary for decentralization to be a Nash equilibrium.…”
Section: Vertical Integration and Decentralizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The economic value (V i ) for a product category i, based on the three components, can be formally derived and is given as (McGuire and Staelin, 1983;Subramaniam and Shaw, 2001;Trivedi, 1998):…”
Section: Technology Lock-in Costsmentioning
confidence: 99%
“…Anderson and Bao [15] considered the chainto-chain competition in which different manufacturers sell through exclusive retailers that compete for end customers. Trivedi [16] found that the competitions at both retailer and manufacturer levels have significant impacts on the members' profits and prices. Wei and Zhao [17] study the pricing and remanufacturing decisions of two competing supply chains with competition at both manufacturer and retailer levels.…”
Section: Introductionmentioning
confidence: 99%